Thinking like Grass, with Deleuze in Education? - Ling, Xiao-Jiu (Journal of the Canadian Association for Curriculum Studies, 2010)
The French philosopher Gilles Deleuze might not be well known yet to the Canadian education landscape. So in this paper, I begin with a close-reading of “On the Superiority of Anglo-American Literature”, a chapter in Deleuze’s collaborative works with his colleague Claire Parnet, appropriately titled Dialogue, where they exemplifies their own “deterritorialization” of thought across disciplines and geographical domains. I then give a sketch of his reflection on the major movements in Philosophy as an attempt to envision his own possible orientation of philosophizing that is close to life in its creative force. By introducing some of the important yet creative concepts as well as the fresh spirit of his philosophical movements in thinking, I intend to create a space of openness where we the educators could think anew on the some fundamental theoretical questions in curriculum studies, for instance: what does it mean to attempt to bring Deleuze’s work from the “outside” in the proximity of our educational realm, or rather, to extend our ignorance to the edge of the inter-disciplinary borders, to think about curriculum questions with his diverse philosophical thinking?